Pengaruh Terapi Slow Stroke Back Massage terhadap Perubahan Tekanan Darah pada Pasien Hipertensi - Utama, Yofa Anggriani (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine the effect of slow stroke back massage therapy on changes in blood pressure in hypertensive patients at the Palembang Clinic. The quantitative research method is a quasi-experimental method, with a one group pre test-post test design on a sample of 30 respondents. The research results showed that systolic blood pressure before and after slow stroke back massage therapy showed that there was an effect of slow stroke back massage intervention on blood pressure in hypertension sufferers at the Rizki Medika Clinic in Palembang.